Evaluating the Al-Alamanah Islamic School Library Using the GOEM Model: Effectiveness and Learning Implications - Fajrina, Farahdiba; Hadiapurwa, Angga; Wulandari, Yayu (Jurnal Tadwin, 2025)
This study aims to evaluate the effectiveness of the MA Al-Amanah Islamic School Library service using the Goal Oriented Evaluation Model (GOEM) approach developed by Ralph W. Tyler. This model was chosen because it emphasizes the achievement of goals as the main indicator of the success of a program. The study was conducted using a qualitative descriptive method through observation, semi-structured interviews with teachers, librarians, and vice principals, and the distribution of open questionnaires to 30 students as respondents. The evaluation results show that the library has contributed significantly to the achievement of learning goals, especially in terms of improving student literacy, character building, and strengthening learning independence. Through the seven stages of the GOEM evaluation, an increase in learning motivation, discipline, and active involvement of students in utilizing library facilities was identified. Although there are still limitations in the support of psychomotor facilities and formal evaluation instruments, the library has functioned as an effective and adaptive learning space for students' information needs. This evaluation also shows the importance of developing digital services and improving librarian competence in assisting the learning process. Thus, the application of a goal-based evaluation model such as GOEM is not only relevant for assessing the effectiveness of services, but is also useful as a reflective tool in strategic planning for the development of school libraries in the future.